2020
DOI: 10.3390/nu12072152
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Aspects and Eating Habits during COVID-19 Home Confinement: Results of EHLC-COVID-19 Italian Online Survey

Abstract: The COVID-19 pandemic has had a huge impact on the population with consequences on lifestyles. The aim of the study was to analyse the relationship between eating habits, mental and emotional mood. A survey was conducted online during social isolation, from 24 April to 18 May 2020, among the Italian population. A total of 602 interviewees were included in the data analysis. A high percentage of respondents experienced a depressed mood, anxious feelings, hypochondria and insomnia (61.3%, 70.4%, 46.2% and 52.2%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

33
357
6
46

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 326 publications
(442 citation statements)
references
References 41 publications
33
357
6
46
Order By: Relevance
“…An Italian study during COVID-19 addressed emotional eating using a subset of items from the Yale food addiction scale. Among 602 individuals (age 18–79 years old), about half the cohort increased their food intake to feel better (55%) and used food in response to anxious feelings (48.7%) [ 46 ]. The study identified women as being more disposed than men to anxiety and to consuming comfort foods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An Italian study during COVID-19 addressed emotional eating using a subset of items from the Yale food addiction scale. Among 602 individuals (age 18–79 years old), about half the cohort increased their food intake to feel better (55%) and used food in response to anxious feelings (48.7%) [ 46 ]. The study identified women as being more disposed than men to anxiety and to consuming comfort foods.…”
Section: Discussionmentioning
confidence: 99%
“…Women were also more likely to report depression; EE (and specific anxiety about it); treatment with drugs and supplements; and having been “on a diet” prior to COVID-19. Younger age, lower BMI (significant for women respondents compared to men), not being anxious, and less food intake for satisfaction were predictors of overfeeding control [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sensory appeal, the taste and presentation of food, may function as a motivator for emotional eating by offering psychological escape and distraction [65]. Aesthetic objects and activities engage our senses, focusing our attention on the experience at hand and taking our minds off of other issues, including the current pandemic situation [109].…”
Section: Discussionmentioning
confidence: 99%
“…Participants’ perceived stress levels, eating behaviors, and food choice motives were assessed in June 2020, two months after the “stay-at-home” order was implemented in at least 42 states in the US. Preliminary research suggests this prolonged homestay may be negatively impacting mental health [ 4 , 35 , 65 ] and dietary behavior changes [ 35 , 65 ]. We hypothesized that the relationship between perceived stress and food choice motives would be mediated by emotional eating ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although limited, most current studies show an increased burden of mental health symptoms among psychiatric patients and healthcare workers and lower psychological well-being in the general population amid the COVID-19 outbreak [ 3 ]. Population-based studies have also revealed a high occurrence of self-reported psychological distress during the early phases of the pandemic in different populations [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%